Silicon-tin-carbon composite material, preparation method thereof, pole piece and electrochemical device
By forming a cluster-like structure and graphene cladding in the silicon-tin composite material, the problem of poor electrochemical performance is solved, better magnification and cycling performance is achieved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202411765467.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
The electrochemical performance of existing silicon-tin composite materials is poor, especially the rate performance and cycle performance.
Silicon-tin carbon composite particles distributed in clustered structures are used, and graphene carbon layer is coated on their surface to form a core-shell structure and a porous structure to improve conductivity and reduce charge transfer internal resistance.
The electrochemical properties of silicon-tin carbon composites are significantly improved, especially in terms of magnification and cyclic properties, and the preparation method is simplified to make them suitable for large-scale production.
Smart Images

Figure CN119517969A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-tin-carbon composite material and a preparation method thereof, a pole piece and an electrochemical device. Background Art
[0002] The emergence of large-scale lithium-ion battery applications represented by hybrid vehicles and stationary utility grids has brought great challenges to the production of lithium-ion batteries, so there is a need to develop lithium-ion batteries based on cheap raw materials and scalable production processes. The slower growth of the electric vehicle market compared to initial expectations does reflect this challenging situation.
[0003] Silicon (Si) and tin (Sn) have attracted extensive attention as anode materials for lithium-ion batteries due to their theoretical capacities of nearly 4200 mAh / g and 990 mAh / g, respectively, which are about 2.5-10 times that of traditional graphite. However, most Si and Sn anodes have limited cycle life due to their extremely large volume expansion (300%). With repeated cycling, the large volume changes of Si and Sn trigger various capacity fading mechanisms, such as pulverization, contact loss between active particles and conductive agents and current collectors, and unstable solid electrolyte interphase (SEI) formation. At present, extensive research has addressed these issues, usually by adopting well-defined Si and Sn nanostructures, including nanowires, nanotubes, nanoparticles, porous structures, and their carbon material composites.
[0004] Chinese patent application CN 113611826A introduces a silicon-tin / carbon embedded porous composite negative electrode material and a preparation method thereof; during the preparation process, a composite nanomaterial in which elemental tin and silicon are mutually embedded is directly formed, and the nanoparticles form a stable cross-linked structure under the action of a binder, and then form a porous carbon layer after carbonization; the tin particles on the surface of the composite material are further formed into a porous structure by acid corrosion; the composite negative electrode material can maintain an initial capacity of about 1750mAh / g and about 900mAh / g at a current of 0.4mA / g and 0.6mA / g, respectively, which is superior to conventional graphite negative electrodes; but the capacity decreases by about 32% after 40 cycles at a current density of 0.4mA / g; in addition, when the current density increases by 0.2mA / g, the capacity retention rate is only 52%, indicating poor performance in rate performance and cycle performance.
[0005] Therefore, it is urgent to propose a scalable and large-scale preparation method to comprehensively improve the performance of silicon-tin materials and show excellent performance in rate and cycle performance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects of poor electrochemical performance of silicon-tin composite materials in the prior art, especially poor rate performance and cycle performance, and provide a silicon-tin-carbon composite material and its preparation method, pole piece and electrochemical device. The silicon-tin-carbon composite material of the present invention has better electrical conductivity and lower charge transfer internal resistance. The battery assembled from the silicon-tin-carbon composite material has better electrochemical performance, especially better rate performance and cycle performance. The preparation method of the silicon-tin-carbon composite material of the present invention is simple, does not involve a large amount of chemical reagents, is highly practical, can be operated on a large scale, and is easy to industrialize.
[0007] The present invention solves the above technical problems through the following solutions.
[0008] The present invention provides a silicon-tin-carbon composite material, which comprises silicon-tin-carbon composite particles distributed in a cluster structure and a graphene carbon layer coated on the surface of the silicon-tin-carbon composite particles distributed in a cluster structure; second pores are distributed between the silicon-tin-carbon composite particles distributed in a cluster structure;
[0009] Among them, a single silicon-tin-carbon composite particle has a core-shell structure, the shell includes a carbon shell layer, and the core includes porous silicon nanoparticles and tin nanoparticles; and a first pore is distributed between the core and the shell.
[0010] In the present invention, the cluster structure means that there are at least two silicon-tin-carbon composite particles in the structure.
[0011] In the present invention, the D50 of the silicon-tin-carbon composite material may be 250-330 nm, preferably 270-310 nm, for example 300, 296, 295, 290, 289, 285 or 280 nm.
[0012] In the present invention, the average pore size of the silicon-tin-carbon composite material may be 15-30 nm, preferably 18-27 nm, for example, 25.2, 24.9, 24.2, 23.9, 23.8, 23.6, 23.2, 23.1, 22.7, 22.2, 21.9, 21.8 or 20.7 nm.
[0013] In the present invention, the silicon content of the silicon-tin-carbon composite material may be 45%-50%, preferably 46%-49%, for example 48.5%, 48.3%, 48.2%, 48.1%, 47.9%, 47.8%, 47.6%, 47.3%, 47.2%, 46.8%, 46.7% or 46.3%.
[0014] In the present invention, the tin content of the silicon-tin-carbon composite material may be 25%-30%, preferably 26%-29%, for example 28.3%, 28.1%, 27.5%, 27.3%, 27.2%, 26.9%, 26.8%, 26.7%, 26.5%, 26.3% or 26.1%.
[0015] In the present invention, the carbon content of the silicon-tin-carbon composite material may be 15%-20%, preferably 16%-19%, for example 18.1%, 18.0%, 17.9%, 17.7%, 17.5%, 17.4%, 17.3%, 17.2% or 17.1%.
[0016] In the present invention, the oxygen content of the silicon-tin-carbon composite material may be 5%-10%, preferably 6%-9%, for example 7.82%, 7.67%, 7.54%, 7.51%, 7.48%, 7.41%, 7.31%, 7.27%, 7.21%, 7.14%, 7.12%, 7.09%, 7.03%, 6.99% or 6.97%.
[0017] The content of each element mentioned above represents the percentage of the mass of each element to the mass of the silicon-tin-carbon composite material.
[0018] In the present invention, the carbon shell layer of the single silicon-tin-carbon composite particle preferably further includes carbon nanotubes and / or heteroatoms.
[0019] The carbon nanotubes may be any conventional type in the art, preferably single-walled carbon nanotubes or multi-walled carbon nanotubes, more preferably double-walled carbon nanotubes, and further preferably alkylated double-walled carbon nanotubes or carboxylated double-walled carbon nanotubes. The alkylated double-walled carbon nanotubes are preferably alkylated double-walled carbon nanotubes having 1 to 20 carbon atoms.
[0020] Wherein, the inner wall diameter of the carbon nanotube is preferably 1-5 nm, such as 2-4 nm.
[0021] The type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen.
[0022] Wherein, when the carbon shell layer of the single silicon-tin-carbon composite particle further includes heteroatoms, the content of the heteroatoms in the silicon-tin-carbon composite material may be 0.1-0.65%, preferably 0.2%-0.55%, for example 0.45%, 0.43%, 0.42%, 0.41%, 0.39%, 0.38%, 0.37%, 0.36%, 0.35%, 0.34%, 0.32% or 0.31%. The content of heteroatoms indicates the percentage of the mass of heteroatoms to the mass of the silicon-tin-carbon composite material.
[0023] The present invention also provides a method for preparing a silicon-tin-carbon composite material, which comprises the following steps:
[0024] S1, mixing an aqueous dispersion of a silicon dioxide-coated silicon-tin alloy material and an oil phase solution containing an emulsifier, removing the solvent, and performing a first heat treatment to obtain a silicon dioxide-coated silicon-tin alloy material distributed in a clustered structure;
[0025] S2, carbon-coating the silicon-tin alloy material coated with silicon dioxide distributed in a cluster structure, removing silicon dioxide, and obtaining silicon-tin-carbon composite particles distributed in a cluster structure;
[0026] S3, coating the silicon-tin-carbon composite particles distributed in a cluster structure with graphene carbon to obtain a silicon-tin-carbon composite material.
[0027] In S1 of the present invention, the aqueous dispersion of the silicon dioxide-coated silicon-tin alloy material preferably comprises the silicon dioxide-coated silicon-tin alloy material, a surfactant and water.
[0028] The method for preparing the silicon dioxide-coated silicon-tin alloy material preferably comprises the following steps: mixing a silicon-tin alloy nanometer precursor, a first silicon source and an ammonia solution, acid washing, and a second heat treatment.
[0029] The D50 of the silicon-tin alloy nano-precursor is preferably 50-80nm, such as 65nm. In the silicon-tin alloy nano-precursor, the mass content of silicon is preferably 55.5%-90.5%, such as 73%, 75% or 80%. In the silicon-tin alloy nano-precursor, the mass content of tin is preferably 9.5%-44.5%, such as 27%, 25% or 20%.
[0030] The silicon-tin nano alloy precursor is preferably obtained by ball milling a second silicon source and a tin source. The type of the second silicon source may be conventional in the art, preferably one or more of silicon powder, silicon oxide and silicon monoxide, such as silicon powder. The D50 of the second silicon source is preferably 50-100nm, such as 70nm. The type of the tin source may be conventional in the art, such as tin powder. The D50 of the tin source is preferably 50-100nm, such as 85nm. The mass ratio of the second silicon source to the tin source is preferably (1-3): (0.3-0.8), such as 1.5: 0.5 or 2: 0.5. The equipment for ball milling may be conventional in the art, such as a ball milling jar. The ball-to-material ratio during ball milling is preferably (30-60): 1, such as 50: 1. The rotation speed of the ball mill is preferably 450-850r / min, such as 600 or 700r / min. The time of ball milling is preferably 6-20h, such as 10 or 14h.
[0031] The type of the first silicon source can be conventional in the art, preferably a silicate or a silicate. The silicate is preferably ethyl orthosilicate and / or methyl orthosilicate. The silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.
[0032] The mass percentage of ammonia in the ammonia solution is preferably 25%-30%, for example 28%.
[0033] The mass volume ratio of the silicon-tin alloy nano-precursor, the first silicon source and the ammonia solution is preferably 3g: (3-10) mL: (240-260) mL, for example 3g: 6 mL: 250 mL or 3g: 8 mL: 250 mL.
[0034] The mixing time is preferably 20-30 hours, such as 24 hours.
[0035] The acid used for pickling can be a conventional inorganic acid in the art, such as hydrochloric acid. The pickling generally uses an aqueous solution of an acid, such as an aqueous solution of an acid with a molar concentration of 2M.
[0036] After the acid washing and before the second heat treatment, it is preferred to further include conventional steps of filtration, washing and drying in the art.
[0037] The temperature of the second heat treatment is preferably 500-700° C., such as 550 or 650° C. The time of the second heat treatment is preferably 2-8 hours, such as 5 hours. The rate of heating from room temperature to the temperature of the second heat treatment is preferably 1-10° C. / min, such as 3° C. / min.
[0038] The surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide.
[0039] Wherein, the ratio of the silicon dioxide-coated silicon-tin alloy material, the surfactant and the water is preferably (3-5) g: (0.3-0.5) mol: 300 mL, for example 4 g: 0.45 mol: 300 mL.
[0040] In S1 of the present invention, the type of the emulsifier may be an emulsifier having a hydrophile-lipophile balance (HLB) of 3-8, preferably an emulsifier having a hydrophile-lipophile balance (HLB) of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate.
[0041] In S1 of the present invention, the type of the oil phase solvent in the oil phase solution containing the emulsifier can be conventional in the art, and is preferably an olefin having 12 to 28 carbon atoms, such as 1-octadecene.
[0042] In S1 of the present invention, the mass percentage of the emulsifier in the oil phase solution containing the emulsifier may be 0.3-0.8wt%, preferably 0.4-0.7wt%, for example 0.6wt%.
[0043] In S1 of the present invention, the mass ratio of the silicon dioxide-coated silicon-tin alloy material to the emulsifier may be 4:(90-280), for example 4:180.
[0044] In S1 of the present invention, the method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 95-98°C.
[0045] In S1 of the present invention, the temperature of the first heat treatment is preferably 450-600° C., for example 550° C. The time of the first heat treatment is preferably 0.5-1.5 h, for example 1 h. The first heat treatment is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen, helium, neon or argon, for example nitrogen.
[0046] In S1 of the present invention, the first heat treatment preferably further includes a condensation step.
[0047] In S2 of the present invention, the type of carbon source for carbon coating can be conventional in the art, preferably phenolic resin and / or asphalt, such as phenolic resin.
[0048] Among them, when the type of the carbon source is phenolic resin, the preparation method of carbon-coating the silicon-tin alloy material coated with silica with a clustered structure preferably includes the following steps: mixing resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silica with a clustered structure, polymerization reaction and coating treatment.
[0049] The molar ratio of the formaldehyde to the resorcinol may be (500-1500): (0.5-1.5), for example, 1000: 1. The catalyst may be a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate. The molar ratio of the resorcinol to the catalyst may be (0.5-1.5): (0.007-0.03), for example, 0.9: 0.01. The ratio of the formaldehyde to the silicon dioxide-coated silicon-tin alloy material distributed in a clustered structure is preferably 0.9 mol: (2-3) g, for example, 0.9 mol: 2.5 g. The temperature of the polymerization reaction may be 80-100° C., for example, 90° C. The time of the polymerization reaction may be 2-10 h, for example, 6 h. After the polymerization reaction and before the coating treatment, a drying step is preferably further included. Among them, the drying operation may be conventional in the art, such as freeze drying, supercritical drying or vacuum drying. The freeze drying temperature may be -30 to -80° C., for example, -60° C. The freeze drying time may be 3-7h, for example 4h. The supercritical drying temperature may be 10-40°C, for example 20 or 30°C. The supercritical drying time may be 1-3h, for example 1.5 or 2h. During the supercritical drying, the pressure of the system may be 10-15kPa, for example 10kPa. The vacuum drying temperature may be 80-100°C, for example 90°C. The vacuum drying time may be 18-24h, for example 20h.
[0050] In S2 of the present invention, the carbon source is preferably further added with carbon nanotubes and / or heteroatoms during the carbon coating.
[0051] Among them, when carbon nanotubes are also added to the carbon source, the preparation method of carbon-coating the silicon-tin alloy material coated with silica with a clustered structure preferably includes the following steps: mixing a surfactant, carbon nanotubes and water, ultrasonically dispersing, then adding resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silica with a clustered structure, mixing, polymerizing and coating.
[0052] The type of the surfactant is preferably one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as cetyltrimethylammonium bromide.
[0053] The type of the carbon nanotube can be conventional in the art, preferably single-walled carbon nanotube or multi-walled carbon nanotube, more preferably double-walled carbon nanotube, further preferably alkylated double-walled carbon nanotube or carboxylated double-walled carbon nanotube. The alkylated double-walled carbon nanotube is preferably an alkyl double-walled carbon nanotube with a carbon number of 1 to 20. The inner wall diameter of the carbon nanotube is preferably 1 to 5 nm, for example 2 to 4 nm.
[0054] The ratio of the surfactant to the carbon nanotubes is preferably (0.2-0.65) mmol: (0.1-0.5) g, such as 0.3 mmol: 0.23 g or 0.5 mmol: 0.23 g.
[0055] The molar ratio of the surfactant to the water is preferably (0.1-0.5):8000, such as 0.3:8000 or 0.5:8000.
[0056] The ultrasonic dispersion time is preferably 30-60 min, such as 45 min.
[0057] Among them, when heteroatoms are also added to the carbon source, the preparation method of carbon-coating the silicon-tin alloy material coated with silica with a clustered structure preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silica with a clustered structure, polymerization reaction and coating treatment.
[0058] The type of the heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the type of the heteroatom is nitrogen, the type of the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as p-nitroaniline.
[0059] The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.5), for example 0.05:0.9.
[0060] Among them, when carbon nanotubes and heteroatoms are also added to the carbon source, the preparation method of carbon-coating the silicon-tin alloy material coated with silica with a clustered structure preferably includes the following steps: mixing a surfactant, carbon nanotubes and water, ultrasonically dispersing, then mixing a heteroatom source, resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silica with a clustered structure, polymerization reaction and coating treatment.
[0061] In S2 of the present invention, the temperature of the carbon coating may be 500-900°C, such as 650 or 750°C.
[0062] In S2 of the present invention, the carbon coating time may be 8-24° C., for example, 15 h.
[0063] In S2 of the present invention, the method for removing silicon dioxide may be etching. The etching solution used for the etching is preferably a hydrofluoric acid solution. The mass percentage of hydrofluoric acid in the hydrofluoric acid solution is preferably 4-6wt%, such as 5wt%.
[0064] In S3 of the present invention, the carbon source used for the graphene coating may be a conventional carbon source capable of forming graphene in the art, preferably humic acid.
[0065] Among them, when the carbon source is humic acid, the graphene carbon coating is preferably performed by mixing the silicon-tin-carbon composite particles distributed in a clustered structure, humic acid and water, and adding ammonia solution dropwise under stirring conditions to remove the solvent.
[0066] The amount of water used is not limited, so that the solid-liquid ratio in the mixed solution of carbon-tin-carbon composite particles, humic acid and water is preferably 1:(10-15), for example 1:12.
[0067] The ammonia content in the aqueous ammonia solution is preferably 25%-30%, for example 28%. The amount of the aqueous ammonia solution used is not limited, as long as the humic acid powder is completely dissolved.
[0068] The method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 80-100°C, such as 95°C.
[0069] In S3 of the present invention, the mass ratio of the silicon-tin-carbon composite particles to the carbon source may be (85-97):(10-18), preferably (88-93):(10-16), for example 90:10 or 90:15.
[0070] In S3 of the present invention, the graphene carbon coating is preferably subjected to a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering.
[0071] The temperature of the first sintering step is preferably 200-350°C, such as 280 or 300°C. The time of the first sintering step is preferably 3-6h, such as 4h. The first sintering step is preferably performed in a microwave oven. The power of the microwave oven can be 800-1100W, such as 1000W.
[0072] The end point of the cooling may be room temperature, generally 20-30°C.
[0073] Wherein, the temperature of the second stage sintering is preferably 500-800°C, such as 600 or 650°C. The time of the second stage sintering is preferably 10-24h, such as 15h. The rate of heating from room temperature to the temperature of the second stage sintering can be 1-10°C / min, such as 3°C / min. The second stage sintering is preferably carried out in a tubular furnace. The second stage sintering is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen.
[0074] The present invention provides a silicon-tin-carbon composite material, which is prepared by the preparation method of the silicon-tin composite material as mentioned above.
[0075] The present invention also provides a pole piece, which comprises the silicon-tin-carbon composite material as described above.
[0076] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0077] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0078] The reagents and raw materials used in the present invention are commercially available.
[0079] The positive and progressive effects of the present invention are:
[0080] (1) The silicon-tin-carbon composite material prepared by the present invention includes silicon-tin-carbon composite particles distributed in a cluster structure and a graphene coating layer; a single silicon-tin-carbon composite particle is a carbon ball with a hollow structure, and porous silicon nanoparticles and tin nanoparticles are encapsulated in the carbon ball, which can alleviate the volume expansion of silicon and tin; pores are distributed between the silicon-tin-carbon composite particles distributed in a cluster structure, which doubly alleviates the volume expansion of silicon and tin; further, the graphene coating layer has good electrical conductivity and mechanical properties, provides another line of defense against the volume expansion of silicon and tin, and can make the silicon-tin-carbon composite material have good electrochemical properties.
[0081] (2) The battery assembled from the silicon-tin-carbon composite material has better electrochemical performance, especially better rate performance and cycle performance.
[0082] (3) The preparation method of the silicon-tin-carbon composite material of the present invention is simple, does not require the involvement of a large amount of chemical reagents, is highly practical, can be operated on a large scale, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 Schematic diagram of the structure of the silicon-tin-carbon composite material prepared in the embodiment.
[0084] Description of reference numerals:
[0085] Silicon-tin-carbon composite particle-1, graphene carbon layer-2, second pore-3, porous silicon nanoparticle-101, tin nanoparticle-102, carbon shell layer-103, first pore-104. DETAILED DESCRIPTION
[0086] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0087] Example 1
[0088] S1. (1) Silicon powder (D50: 70 nm) and tin powder (D50: 85 nm) were added into a ball mill at a mass ratio of 1.5:0.5, with a ball-to-material ratio of 50:1, a ball milling speed of 600 r / min, and a ball milling time of 14 h to obtain a silicon-tin alloy nano-precursor; wherein the D50 of the silicon-tin alloy nano-precursor is 65 nm, and the mass content of silicon in the silicon-tin alloy nano-precursor is 75%, and the mass content of tin is 25%.
[0089] (2) 6 mL of tetraethyl orthosilicate and 3 g of silicon-tin alloy nano-precursor were added to 250 mL of 28% ammonia solution in sequence, mixed and stirred for 24 h, filtered and washed, and pickled with 2 mol / L hydrochloric acid, then filtered, washed and dried; then, the silica layer was fixed by a second heat treatment at 550 °C with a heating rate of 3 °C / min for 5 h, thereby obtaining a silica-coated silicon-tin alloy material.
[0090] (3) 4 g of the silica-coated silicon-tin alloy material was uniformly dispersed in 300 mL of deionized water containing 0.45 mol of a surfactant (hexadecyltrimethylammonium bromide) to form an aqueous dispersion, and the dispersion was mixed with 300 mL of a 1-octadecene solution containing 0.6 wt % of diethylene glycol monooleate to form an oil-in-water emulsion. After evaporating the solvent at 95-98°C, the mixture was collected by centrifugation and then first heat-treated at 550°C in an inert atmosphere (nitrogen) for 1 h to remove organic matter. The dispersion was then condensed to obtain a silica-coated silicon-tin alloy material having a clustered structure.
[0091] S2. (1) 0.3 mmol surfactant (hexadecyltrimethylammonium bromide), 0.23 g carboxylated double-walled carbon nanotubes (purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with an inner wall diameter of 2-4 nm) and 8 mol deionized water were mixed and ultrasonically dispersed for 45 min to form spherical micelles for fixation.
[0092] (2) Add 0.05mmol of p-nitroaniline (purchased from Wujiang Huaxu Chemical Technology Co., Ltd.), 0.9mmol of resorcinol, 0.9mol of formaldehyde and 0.01mmol of sodium carbonate, and continue stirring. Subsequently, add 2.5g of silicon dioxide-coated silicon-tin alloy material with clustered structure distribution. Then polymerize at 90℃ for 6h, and then vacuum dry at 90℃ for 18h, and then coat at 750℃ for 15h in a nitrogen atmosphere. Finally, remove the silicon dioxide with 5wt% HF solution to form a void space, and obtain silicon-tin-carbon composite particles with clustered structure distribution.
[0093] S3. The silicon-tin-carbon composite particles with clustered structure distribution are mixed with humic acid in a mass ratio of 90:10, and added into deionized water for uniform mixing, and the solid-liquid ratio is controlled at 1:12. Then, a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved. The mixture is heated to 95°C and the solvent is evaporated to make the humic acid uniformly coated on the surface of the silicon-tin-carbon composite particles with clustered structure distribution. The mixture is sintered at 300°C in a microwave oven (microwave power of 1000 W) for 4 hours, cooled to room temperature, taken out, and then placed in a tubular furnace under an inert atmosphere and heated from room temperature to 600°C at a rate of 3°C / min for 15 hours. The humic acid is thermally decomposed to synthesize graphene in situ to obtain a silicon-tin-carbon composite material.
[0094] Example 2
[0095] The difference from Example 1 is that in step S1 (1), the mass ratio of silicon powder to tin powder is 2:0.5; wherein the D50 of the silicon-tin nano alloy precursor is 65 nm, and the mass content of silicon in the silicon-tin nano alloy precursor is 80%, and the mass content of tin is 20%.
[0096] Example 3
[0097] The difference from Example 1 is that the ball milling speed in step S1 (1) is 700 r / min.
[0098] Example 4
[0099] The difference from Example 1 is that the ball milling time in step S1 (1) is 10 h.
[0100] Example 5
[0101] The difference from Example 1 is that the silicon source in step S1 (2) is methyl orthosilicate.
[0102] Example 6
[0103] The difference from Example 1 is that 8 mL of tetraethyl orthosilicate is added in step S1 (2).
[0104] Example 7
[0105] The difference from Example 1 is that the second heat treatment temperature in step S1 (2) is 650°C.
[0106] Example 8
[0107] The difference from Example 1 is that in step S1 (3), a 0.6 wt % 1-octadecene solution of diethylene glycol monooleate is used.
[0108] Example 9
[0109] The difference from Example 1 is that the emulsifier in step S1 (3) is glyceryl monostearate.
[0110] Example 10
[0111] The difference from Example 1 is that the surfactant in step S2 (1) is 0.55 mmol.
[0112] Embodiment 11
[0113] The difference from Example 1 is that 0.5 mmol of resorcinol is added in step S2 (2).
[0114] Example 12
[0115] The difference from Example 1 is that in step S2 (2), 3 g of silicon dioxide-coated silicon-tin alloy material distributed in a clustered structure is added.
[0116] Example 13
[0117] The difference from Example 1 is that the polymerization temperature in step S2 (2) is 85°C.
[0118] Embodiment 14
[0119] The difference from Example 1 is that the coating treatment temperature in step S2 (2) is 650°C.
[0120] Embodiment 15
[0121] The difference from Example 1 is that in step S3, the mass ratio of the silicon-tin-carbon composite particles distributed in a cluster structure to the humic acid is 90:15.
[0122] Example 16
[0123] The difference from Example 1 is that the temperature of the first sintering in step S3 is 280°C.
[0124] Embodiment 17
[0125] The difference from Example 1 is that the temperature of the second stage sintering in step S3 is 650°C.
[0126] Comparative Example 1
[0127] The only difference from Example 1 is that the raw material is pure silicon powder only.
[0128] Comparative Example 2
[0129] The only difference from Example 1 is that the raw material is pure tin powder
[0130] Comparative Example 3
[0131] The only difference from Example 1 is that no tin powder is added in step S1 (1).
[0132] Comparative Example 4
[0133] The only difference from Example 1 is that silicon powder is not added in step S1 (1).
[0134] Comparative Example 5
[0135] The only difference from Example 1 is that steps S1 (3), S2 (1) and S2 (2) are omitted.
[0136] Comparative Example 6
[0137] The only difference from Embodiment 1 is that step S1 (3) is omitted.
[0138] Effect Example 1
[0139] The schematic diagram of the structure of the silicon-tin-carbon composite material obtained in Examples 1-17 is as follows Figure 1 shown. Figure 1 Part a is a schematic diagram of the overall structure of the silicon-tin-carbon composite material. Figure 1 Part b is a schematic diagram of the structure of a single silicon-tin-carbon composite particle. Figure 1 It can be seen that the silicon-tin-carbon composite material includes silicon-tin-carbon composite particles 1 distributed in a cluster structure and a graphene carbon layer 2 coated on the surface of the silicon-tin-carbon composite particles distributed in a cluster structure; second pores 3 are distributed between the silicon-tin-carbon composite particles 1 distributed in a cluster structure; a single silicon-tin-carbon composite particle 1 has a core-shell structure, the shell includes a carbon shell layer 103, and the core includes porous silicon nanoparticles 101 and tin nanoparticles 102; and first pores 104 are distributed between the core and the shell.
[0140] XRF was used to test the element content (silicon, tin, carbon, oxygen and nitrogen content) in the silicon-tin-carbon composite material prepared by the present invention. The test method was microwave digestion, and the silicon-tin-carbon composite material prepared in the embodiment or comparative example was pre-treated: 2±0.05g of stearic acid and 6±0.5g of the silicon-tin-carbon composite material prepared in the embodiment or comparative example were mixed and ground, pressed into tablets, and then tested in the Avio™ 200 device; test conditions: air pressure was 2.5MPa.
[0141] The D50 of the silicon-tin-carbon composite materials prepared in the examples and comparative examples was tested using a Malvern particle size tester.
[0142] The conductivity was measured at room temperature using an Orion Star™ A212 conductivity benchtop meter.
[0143] The average pore size was measured using a POROLUX Cito instrument.
[0144] The charge transfer resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm3 )get.
[0145] The above physical and chemical results are shown in Table 1 below.
[0146] Table 1
[0147]
[0148] Table 1 continued
[0149]
[0150] Note: The content of each element in the above table represents the percentage of the mass of each element in the total mass of the silicon-tin-carbon composite material.
[0151] Effect Example 2
[0152] The preparation method of the button cell used for testing the electrochemical performance is as follows: the silicon-tin-carbon composite material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.60 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte using 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is PE / PP / PE composite film, and assembled into a button battery.
[0153] The above button cell was subjected to various electrical performance tests on a blue battery tester, the test condition was 25°C, and the charging voltage limit was 0.005-2V.
[0154] (1) First discharge specific capacity and first coulombic efficiency
[0155] The charge and discharge were carried out at a rate of 0.1C, and the first discharge specific capacity and the first coulombic efficiency were tested. The test results are shown in Table 2.
[0156] (2) Cycle performance
[0157] The charge and discharge cycles were performed 300 times at a rate of 0.1C, and the 300th discharge specific capacity was recorded as the 300-cycle retention capacity. The test results are shown in Table 2.
[0158] Table 2
[0159]
[0160] (3) Rate performance
[0161] The test conditions for rate performance are: rate charge and discharge at a current density of 0.1 mA / g-3 mA / g, and the charging voltage is limited to 0.005-2 V. The rate performance is tested at a current density of 0.1 mAh / g. The results are shown in Table 3.
[0162] Table 3
[0163]
[0164] It can be seen from Table 2 and Table 3 that, compared with Comparative Examples 1-6, Example 1-17 obtains a silicon-tin alloy material coated with silicon dioxide having a cluster structure, and then obtains a silicon-tin-carbon composite material by carbon coating and graphene coating. In the silicon-tin-carbon composite material obtained in Example 1-17, tin nanoparticles and porous silicon nanoparticles are co-encapsulated in hollow carbon spheres, which can alleviate the volume expansion of silicon and tin; there are also pores between the individual particles that make up the cluster structure, which can doubly alleviate the volume expansion of silicon and tin; further, the in-situ coating of graphene enhances the electrical conductivity and mechanical properties of the silicon-tin-carbon composite material, and further improves its volume expansion defect. Therefore, the silicon-tin-carbon composite material obtained in Example 1-17 has better first coulomb efficiency, cycle performance and rate performance than the silicon-tin-carbon composite material obtained in Comparative Examples 1-6.
Claims
1. A silicon-tin-carbon composite material, characterized in that: It comprises silicon-tin-carbon composite particles distributed in a cluster structure and a graphene carbon layer coated on the surface of the silicon-tin-carbon composite particles distributed in a cluster structure; second pores are distributed between the silicon-tin-carbon composite particles distributed in a cluster structure; Among them, a single silicon-tin-carbon composite particle has a core-shell structure, the shell includes a carbon shell layer, and the core includes porous silicon nanoparticles and tin nanoparticles; and a first pore is distributed between the core and the shell.
2. The silicon-tin-carbon composite material according to claim 1, characterized in that The silicon-tin-carbon composite material satisfies one or more of the following conditions a-f: a. The average pore size of the silicon-tin-carbon composite material is 15-30 nm, preferably 18-27 nm, for example, 25.2, 24.9, 24.2, 23.9, 23.8, 23.6, 23.2, 23.1, 22.7, 22.2, 21.9, 21.8 or 20.7 nm; b. The silicon content of the silicon-tin-carbon composite material is 45%-50%, preferably 46%-49%, for example 48.5%, 48.3%, 48.2%, 48.1%, 47.9%, 47.8%, 47.6%, 47.3%, 47.2%, 46.8%, 46.7% or 46.3%; c. The tin content of the silicon-tin-carbon composite material is 25%-30%, preferably 26%-29%, for example 28.3%, 28.1%, 27.5%, 27.3%, 27.2%, 26.9%, 26.8%, 26.7%, 26.5%, 26.3% or 26.1%; d. The carbon content of the silicon-tin-carbon composite material is 15%-20%, preferably 16%-19%, for example 18.1%, 18.0%, 17.9%, 17.7%, 17.5%, 17.4%, 17.3%, 17.2% or 17.1%; e. The oxygen content of the silicon-tin-carbon composite material is 5%-10%, preferably 6%-9%, for example 7.82%, 7.67%, 7.54%, 7.51%, 7.48%, 7.41%, 7.31%, 7.27%, 7.21%, 7.14%, 7.12%, 7.09%, 7.03%, 6.99% or 6.97%; f. The carbon shell layer of the single silicon-tin-carbon composite particle further includes carbon nanotubes and / or heteroatoms; Wherein, the inner wall diameter of the carbon nanotube is preferably 1-5 nm, for example 2-4 nm; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; When the carbon shell layer of the single silicon-tin-carbon composite particle also includes heteroatoms, the content of the heteroatoms in the silicon-tin-carbon composite material is preferably 0.1-0.65%, more preferably 0.2%-0.55%, for example 0.45%, 0.43%, 0.42%, 0.41%, 0.39%, 0.38%, 0.37%, 0.36%, 0.35%, 0.34%, 0.32% or 0.31%.
3. A method for preparing a silicon-tin-carbon composite material, characterized in that: It includes the following steps: S1, mixing an aqueous dispersion of a silicon dioxide-coated silicon-tin alloy material and an oil phase solution containing an emulsifier, removing the solvent, and performing a first heat treatment to obtain a silicon dioxide-coated silicon-tin alloy material distributed in a clustered structure; S2, carbon-coating the silicon-tin alloy material coated with silicon dioxide distributed in a cluster structure, removing silicon dioxide, and obtaining silicon-tin-carbon composite particles distributed in a cluster structure; S3, coating the silicon-tin-carbon composite particles distributed in a cluster structure with graphene carbon to obtain a silicon-tin-carbon composite material.
4. The method for preparing the silicon-tin-carbon composite material according to claim 3, characterized in that: The preparation method of the silicon-tin-carbon composite material satisfies one or more of the following conditions ak: a. In S1, the aqueous dispersion of the silicon dioxide-coated silicon-tin alloy material comprises a silicon dioxide-coated silicon-tin alloy material, a surfactant and water; b. In S1, the type of the emulsifier is an emulsifier with a hydrophile-lipophile balance value of 3-8, preferably an emulsifier with a hydrophile-lipophile balance value of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate; c. In S1, the oil phase solvent in the oil phase solution containing the emulsifier is an olefin having 12 to 28 carbon atoms, such as 1-octadecene; d. In S1, the mass percentage of the emulsifier in the oil phase solution containing the emulsifier is 0.3-0.8wt%, preferably 0.4-0.7wt%, for example 0.6wt%; e. In S1, the mass ratio of the silicon dioxide-coated silicon-tin alloy material to the emulsifier is 4:(90-280), for example, 4:180; f. In S1, the temperature of the first heat treatment is 450-600° C., for example, 550° C.; g. In S1, the first heat treatment time is 0.5-1.5h, for example 1h; h. In S2, the carbon source during carbon coating is phenolic resin and / or asphalt, such as phenolic resin; i. In S2, the carbon source during carbon coating also includes carbon nanotubes and / or heteroatoms; j. In S2, the carbon coating temperature is 500-900°C, for example, 650 or 750°C; k. In S2, the carbon coating time is 8-24°C, for example, 15h.
5. The method for preparing the silicon-tin-carbon composite material according to claim 4, characterized in that: The preparation method of the silicon-tin-carbon composite material satisfies one or more of the following conditions ad: a. In S1, the method for preparing the silicon dioxide-coated silicon-tin alloy material comprises the following steps: mixing a silicon-tin alloy nano-precursor, a first silicon source and an ammonia solution, acid washing, and a second heat treatment; Wherein, the D50 of the silicon-tin alloy nano-precursor is preferably 50-80nm, such as 65nm; the mass content of silicon in the silicon-tin alloy nano-precursor is preferably 55.5%-90.5%, such as 73%, 75% or 80%; the mass content of tin in the silicon-tin alloy nano-precursor is preferably 9.5%-44.5%, such as 27%, 25% or 20%; Wherein, the type of the first silicon source is preferably a silicate or a silicate; the silicate is preferably ethyl orthosilicate and / or methyl orthosilicate; the silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate; The mass volume ratio of the silicon-tin alloy nano-precursor, the first silicon source and the ammonia solution is preferably 3g: (3-10) mL: (240-260) mL, for example 3g: 6 mL: 250 mL or 3g: 8 mL: 250 mL. The temperature of the second heat treatment is preferably 500-700°C, such as 550 or 650°C; the time of the second heat treatment is preferably 2-8h, such as 5h; the rate of heating from room temperature to the temperature of the second heat treatment is preferably 1-10°C / min, such as 3°C / min; b. In S1, the type of the surfactant is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, for example, hexadecyltrimethylammonium bromide; c. In S1, the ratio of the silicon dioxide-coated silicon-tin alloy material, the surfactant and the water is (3-5) g: (0.3-0.5) mol: 300 mL, for example, 4 g: 0.45 mol: 300 mL; d. In S2, when the type of the carbon source is phenolic resin, the preparation method of carbon-coating the silicon-tin alloy material coated with silicon dioxide distributed in a clustered structure comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silicon dioxide distributed in a clustered structure, polymerizing and coating; Among them, the molar ratio of the formaldehyde to the resorcinol is preferably (500-1500): (0.5-1.5), for example, 1000:1; the catalyst is preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate; the molar ratio of the resorcinol to the catalyst is preferably (0.5-1.5): (0.007-0.03), for example, 0.9: 0.01; the ratio of the formaldehyde to the silicon dioxide-coated silicon-tin alloy material distributed in a clustered structure is preferably 0.9 mol: (2-3) g, for example, 0.9 mol: 2.5 g; the temperature of the polymerization reaction is preferably 80-100°C, for example, 90°C; the time of the polymerization reaction is preferably 2-10h, for example, 6h.
6. The method for preparing the silicon-tin-carbon composite material according to claim 4, characterized in that: The preparation method of the silicon-tin-carbon composite material satisfies any one of the following conditions ac: a. When carbon nanotubes are also added to the carbon source, the method for preparing the silicon-tin alloy material coated with silicon dioxide having a clustered structure by carbon coating comprises the following steps: mixing a surfactant, carbon nanotubes and water, ultrasonically dispersing, adding resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silicon dioxide having a clustered structure, mixing, polymerizing and coating; Wherein, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; Wherein, the ratio of the surfactant to the carbon nanotubes is preferably (0.2-0.65) mmol: (0.1-0.5) g, such as 0.3 mmol: 0.23 g or 0.5 mmol: 0.23 g; b. When heteroatoms are added to the carbon source, the method for preparing the silicon-tin alloy material coated with silicon dioxide having a clustered structure by carbon coating comprises the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silicon dioxide having a clustered structure, polymerizing and coating; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; when the type of the heteroatom is nitrogen, the type of the nitrogen source is preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as p-nitroaniline; Wherein, the molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.5), for example, 0.05:0.9; c. When carbon nanotubes and heteroatoms are also added to the carbon source, the preparation method of carbon-coating the silicon-tin alloy material coated with silica having a clustered structure includes the following steps: mixing a surfactant, carbon nanotubes and water, ultrasonically dispersing, then mixing a heteroatom source, resorcinol, formaldehyde, a catalyst and the silicon-tin alloy material coated with silica having a clustered structure, polymerization reaction and coating treatment.
7. The method for preparing the silicon-tin-carbon composite material according to claim 4, characterized in that: The preparation method of the silicon-tin-carbon composite material satisfies one or more of the following conditions ac: In a and S3, the carbon source used in the graphene coating is a carbon source capable of forming graphene, preferably humic acid; Wherein, when the carbon source is humic acid, the graphene carbon coating is preferably performed by mixing the silicon-tin-carbon composite particles distributed in a clustered structure, humic acid and water, and adding an ammonia solution dropwise under stirring to remove the solvent; b. The mass ratio of the silicon-tin-carbon composite particles to the carbon source is (85-97):(10-18), preferably (88-93):(10-16), for example 90:10 or 90:15; c. The graphene carbon coating is subjected to a first-stage sintering, cooling and a second-stage sintering, wherein the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering; The temperature of the first sintering step is preferably 200-350°C, such as 280 or 300°C; the time of the first sintering step is preferably 3-6h, such as 4h; the first sintering step is preferably carried out in a microwave oven; the power of the microwave oven is preferably 800-1100W, such as 1000W; Wherein, the cooling end point is preferably 20-30°C; Among them, the temperature of the second stage sintering is preferably 500-800°C, such as 600 or 650°C; the time of the second stage sintering is preferably 10-24h, such as 15h; the rate of heating from room temperature to the temperature of the second stage sintering is preferably 1-10°C / min, such as 3°C / min; the second stage sintering is preferably carried out in a tubular furnace; the second stage sintering is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen.
8. A silicon-tin-carbon composite material, characterized in that: The silicon-tin-carbon composite material is prepared by the preparation method of any one of claims 3 to 7.
9. A pole piece, characterized in that: It comprises the silicon-tin-carbon composite material as described in any one of claims 1-2 or 8.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Silicon tin / carbon embedded porous composite negative electrode material and preparation method thereof
CN113611826A